Smoking prevalence and intensity in non-organized male population with cardiovascular disease - E. V. Akimova; V. A. Kusnetsov; V. V. Gafarov; M. M. Kayumova; V. Yu. Smaznov (Кардиоваскулярная терапия и профилактика)
Aim. To study tobacco smoking prevalence and intensity in working-age Tumen City men with diagnosed cardiovascular disease (CVD). Material and methods. A representative sample of 25-64-year-old men to undergo cardiac screening was randomly selected from Tumen City voting lists. The examination included two blood pressure (BP) measurements and registration electrocardiogram, with Minnesota coding. Smoking survey was performed according to the WHO protocol. Results. The prevalence of coronary heart disease (CHD) was 11,7%, arterial hypertension (AH) – 50,4%. In CHD men, the percentage of occasional smokers was reduced, and the percentage of ex-smokers was increased. In AH men, regular smoking rates and higher smoking intensity were observed. Increased smoking intensity was associated with significantly elevated systolic BP (SBP), and in higher smoking intensity group – also with increased diastolic BP, mostly among AH patients. In all population, smoking intensity directly correlated with mean SBP level, in 35-44-year-olds. Conclusion. The results obtained should be used for complex CVD prevention in open Tumen City population, with prevention programs based on behavioral risk factor control by both population and high-risk strategies.